Increased Customer Loyalty: The Role Of Service Quality, Trust, Satisfaction, And Business Process Improvement As Mediation - Tjahjono, ST Prijono Budi; Dahlan, Kandi Sofia Senastri (Al-Makki Publisher, 2023)
This study aims to analyze more deeply the relationship and influence of Service Quality, Customer Trust, and Satisfaction on Customer Loyalty of Non-Program Small Medium Enterprise (SME) Credit Customers Mediated by Business Process Improvement (Empirical Study: Bank BTN Regional Office 2). An online survey using Google Forms to SME credit customers of Bank BTN Regional Office 2 covering DKI Jakarta and Banten was used to collect data as material for this study. In this study the variables Service Quality, Customer Trust and Satisfaction as dependent variables, Customer Loyalty as an independent variable, and Business Process Improvement as mediation variables. 226 respondents met the respondent criteria. This study used Partial Least Square SEM also called PLS-SEM. The results prove that Service Quality affects Business Process Improvement, Trust affects Business Process Improvement, Customer Satisfaction affects Business Process Improvement, Service Quality affects Customer Loyalty, Trust does not directly affect Customer Loyalty, Customer Satisfaction does not directly affect Customer Loyalty, Business Process Improvement affects Loyalty Customers, Business Process Improvement affects mediating Service Quality on Customer Loyalty, Business Process Improvement affects mediating Trust in Customer Loyalty, and Business Process Improvement has an effect on mediating Customer Satisfaction with Customer Loyalty.